Effect of static magnetic field on microstructure and mechanical property of AlSi10Mg alloy by laser directed energy deposition - Weiming Niu; Bingke Song; Jiasen Han; Haiou Yang; Zhaopu Yao; Hui Chen; Xin Lin (Journal of Materials Research and Technology)
Laser directed energy deposition (LDED) is one of the popular metal additive manufacturing techniques. However, owing to the steep temperature gradient in melt pool, its as-built part is featured by coarse columnar crystal structures which is detrimental for the mechanical properties. This work uses an infrared laser with a wavelength of 960 nm to conduct the LDED process of AlSi10Mg alloy, where magnetic field with various intensities is employed to tailor the macroscopic morphology, microstructure and mechanical properties of the processed sample. The results show that with the static magnetic field, the melted single track becomes narrower and higher with a corresponding larger wetting angle, changing the stability and quality of layer-by-layer deposition. This can be attributed to the weakened outward Marangoni melt pool flow by the magnetic damping effect. When the magnetic field intensity goes from 0 to 0.2 T, the average grain size decreases from 58.1 μm to 44.1 μm. The magnetic field is effective in refining grain structures and promoting the columnar-to-equiaxed transition of LDED process, while its influence on fusion defects of pores is not remarkable. Due to the thermoelectric-magnetic effect, the volume force imposed on the dendrite is sufficient to fracture the dendrite arm and then reduce the dendrite spacing. In addition, the magnetic field can increase the elongation of AlSi10Mg alloy from 3.5 ± 0.2% to 5.5 ± 0.2% because of the refinement of the grains and the primary dendrite arm spacing. The study provides new insights into the potential of using magnetic field during LDED process to improve the microstructure and mechanical property of AlSi10Mg alloy.